2010
DOI: 10.1039/c0ee00030b
|View full text |Cite
|
Sign up to set email alerts
|

Composite photoanodes for photoelectrochemical solar water splitting

Abstract: Photoelectrochemical (PEC) water splitting is an attractive approach to capturing and storing the earth's abundant solar energy influx. The challenging four-electron water-oxidation half-cell reaction has hindered this technology, giving rise to slow water oxidation kinetics at the photoanode surfaces relative to competitive loss processes. In this perspective, we review recent efforts to improve PEC efficiencies by modification of semiconductor photoanode surfaces with water-oxidation catalysts that can opera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
186
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 268 publications
(194 citation statements)
references
References 101 publications
2
186
0
Order By: Relevance
“…However, OER pathways can be complex and impose significant kinetic bottlenecks. To address this challenge, increasing efforts have been devoted to developing OER catalysts possessing high activity, long-term durability, and low cost, a combination of attributes that is most commonly obtained with first row transition metal oxides (10,11,12,13,14,15,16,17). Among OER catalysts, Co oxides (CoO x ) have been shown to possess desirable activity over a broad range of pH values (12,16,18), from near-neutral to alkaline conditions.…”
Section: Introductionmentioning
confidence: 99%
“…However, OER pathways can be complex and impose significant kinetic bottlenecks. To address this challenge, increasing efforts have been devoted to developing OER catalysts possessing high activity, long-term durability, and low cost, a combination of attributes that is most commonly obtained with first row transition metal oxides (10,11,12,13,14,15,16,17). Among OER catalysts, Co oxides (CoO x ) have been shown to possess desirable activity over a broad range of pH values (12,16,18), from near-neutral to alkaline conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond ~1400 mV, rapid increase in cathodic current represents the occurrence of hydrogen evolution or electrolysis of water as it is well known that the minimum standard potential required for electrolysis of water is about 1.23 V [23]. The current peaks with varying height show formation of H 2 bubbles on the cathode and subsequent release from the surface.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Intense current research efforts have been aimed at optimizing PEC performance by controlling the hematite structure, morphology, and surface chemistry and understanding fundamental charge carrier dynamics. 2,3,7,9,10 Despite these efforts, little is known about the spectral signatures and dynamics of photogenerated electrons and holes in these electrodes under water oxidation conditions. 11 An early study by radiolysis showed that reduced hematite colloidal particles have a broad absorption band above 500 nm due to the conduction band or trapped electrons.…”
mentioning
confidence: 99%